PENGARUH KUALITAS INFORMASI, KEMAMPUAN INDIVIDU DAN NORMA SUBJEKTIF TERHADAP MINAT MAHASISWA DALAM MENGGUNAKAN INTERNET SEBAGAI SUMBER REFERENSI - Purbowati, Monica Jeniestasari Nindia; Herawati, Tubandrijah (Jurnal Ilmiah Mahasiswa FEB, 2013)
This purpose of this study is to test and describe of information quality, individual capability, and subjective norms on affect the students intention in using internet. This research become an interesting  problem because there has not been consistent empirical result. Data of this research is taken through the questionnaire.  This study received 100 responses of S1, S2, S3 students from FEB UB. This research using Updated Information System Succes Model, Kognitif Social Theory,  Technology Acceptance Model (TAM). This research is analyzed by multiple regressions as one of the analysis model. The results indicated that information quality, individual capability and subjective norms positively and significantly affect the students intention in using internet as literature source.Keywords: information quality, individual capability, subjective norms and the  students intention in using internet.